2018
DOI: 10.21608/ejprs.2018.79710
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Conchal Cartilage Grafts and Split Rib Grafts in the Reconstruction of Orbital Floor Fractures

Abstract: Background: Orbital floor fractures always represent a challenge for reconstruction. Various techniques for treatment had evolved over the past years, each with their strengths and weaknesses. The main aim of surgical repair is to relocate herniated orbital tissue and fat back into the orbit restoring both the function and aesthetic aspect. Reconstruction of orbital floor can be performed using various types of materials, either autologous as rib grafts or cartilage grafts or alloplastic as titanium mesh. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These articles were filtered for relevance and duplication, resulting in 46 articles. A full-text assessment was then performed, which reduced the number of articles to 16 articles 13 , 14 , 23 36 . With regards to quality of evidence, all of the studies which were eligible for inclusion were considered to be of moderate quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These articles were filtered for relevance and duplication, resulting in 46 articles. A full-text assessment was then performed, which reduced the number of articles to 16 articles 13 , 14 , 23 36 . With regards to quality of evidence, all of the studies which were eligible for inclusion were considered to be of moderate quality.…”
Section: Resultsmentioning
confidence: 99%
“…In orbital defects between 1.5 and 2 cm 2 , Mohamed et al . 36 found that bilateral sutured conchal cartilages helped overcome some of the problems which may arise from such large defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reconstruction of orbital floor and restoration of volume can be performed using various types of materials, either autologous as bone grafts, cartilage grafts, and fat graft or alloplastic as titanium mesh [20,21]. The most used material was titanium, has the highest tensile strength despite easily bending, and it is compatible with radiographic imaging with a low risk of infection [21,22].…”
Section: Discussionmentioning
confidence: 99%